Pendampingan Baca Tulis Alquran Anak Melalui Metode Qiroati di Musholla Al-Ikhlas Pakalongan Sampang - Arofiq Arofiq; Muhammad Yusron Maulana El-Yunusi (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Public ignorance about education in reading and writing the Al-Quran, is characterized by the number of teachers being disproportionate to the number of students learning to read and write the Al-Quran at the Al-Ikhlas Pakalongan Sampang prayer room, resulting in learning outcomes not meeting expectations. Teacher assistance measures students' understanding of reading and writing the Koran, including verses, pronunciation, rhythm, and correct recitation rules. With the ABCD (Asset Based Community Driven Development) approach, this very effective learning to read the Al-Qur'an is carried out through repetition, question and answer methods, deepening the material, and writing, which aims to truly empower the ability to read the Al-Qur'an students optimally. The Al-Ikhlas prayer room educates many elementary school children. This assistance is intended to assess the extent of the ability to read the Koran at the Al-Ikhlas Pakalongan Sampang Prayer Room, using the Qiroati method, where children know and understand how to read the Koran correctly with tartil rhythm. The Qiroati method plays a very important role in learning to read and write the Koran at the Al-Ikhlas prayer room, Pakalongan. The results of this assistance show that children are enthusiastic about participating in learning using the Qiroati method so that children are able to read the Koran fluently according to correct recitation rules and knowledge.